IDENTIFIKASI PREDIKTOR POLA HIDUP BERSIH DAN SEHAT SISWA SEKOLAH MENENGAH: EKSPLORASI DATA SEKUNDER LOMBA SEKOLAH SEHAT - Tagor Alamsyah Harahap; Asep Saefuddin; Etty Riani; Bambang Indriyanto (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Strengthening character education becomes important thing nowadays as stated in Presidential Decree No. 87 year 2017. Student’s clean and healthy lifestyle reflects from their mind and character. To implement the character education, there are many factors involved in it. The purpose of this research is to identify the variable predictors of student’s clean and healthy environment considering teacher role model variables as intervening variables. The analysis of this relationship pattern is based on an interactionist perspective arguing that student behavior does not occur in isolation, but as an impact of interaction results. School environment is faced daily by students. The intensity of this interaction can lead to healthy and hygienic behavior habits through teacher’s role model. Regression analysis used to prove the perspective of interactionist is based on secondary data of Healthy School Competition period 2016 and 2017. This competition is a junior high school and high school/vocational school competitions representing the province to be included in the national competition. The data used in this study comes from an observation instrument filled by Healthy School Competition Officers at the National level, and students at schools designated as provincial representatives. Students who were selected as subjects were selected randomly. By using regression analysis, empirical tendency showed that school environment factor namely clean and healthy environment become predictor to the formation of student’s clean and healthy behaviour.